2017
DOI: 10.1016/j.still.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the “profil cultural” method for an improved assessment of soil structure under no-till

Abstract: CT3 ; EnjS3 ; Département EAIn France, agronomists have studied the effects of cropping systems on soil structure using a field method that is based on a visual description of the soil structure. This “profil cultural” method was designed as a field diagnostic tool to identify the effects of tillage and compaction on soil structure dynamics. It is of great benefit to agronomists seeking to improve crop management and preserve soil structure and fertility. However, the “profil cultural” method was developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Soil morphostructural characterization is essential to assess SQ since changes in properties, such as aggregate size, type, and development, affect soil permeability, aeration as well as root growth and microorganism development (Boizard et al, 2017;Silva et al, 2014). Thus, the cultural profile method to identify soil structural changes resulting from agricultural practices and evaluate the effects on soil conservation and quality (Silva et al, 2014) are of great importance, as in the intercropped areas evaluated in this study.…”
Section: Soil Penetration Resistance (Pr)mentioning
confidence: 99%
“…Soil morphostructural characterization is essential to assess SQ since changes in properties, such as aggregate size, type, and development, affect soil permeability, aeration as well as root growth and microorganism development (Boizard et al, 2017;Silva et al, 2014). Thus, the cultural profile method to identify soil structural changes resulting from agricultural practices and evaluate the effects on soil conservation and quality (Silva et al, 2014) are of great importance, as in the intercropped areas evaluated in this study.…”
Section: Soil Penetration Resistance (Pr)mentioning
confidence: 99%
“…The cultivated layer is subject to considerable spatial variability, unlike horizons that are not usually affected by tillage (Neves et al, 2003;Fuentes-Llanillo, 2013;Gonçalves et al, 2013;Tavares Filho et al, 2014;Boizard et al, 2016). This variability often allows plants to grow in compacted soils, taking advantage of the flow of water and gas through structural discontinuities (cracks) that also allow root growth (Neves et al, 2003;Reichert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this method of soil profile analysis can be helpful in qualitative evaluation of soil management (Coulomb et al, 1993;Roger-Estrade et al, 2000b;Mueller et al, 2009;Mueller et al, 2013;Munkholm et al, 2013;Guimarães et al, 2013;Tavares Filho et al, 2014;Boizard et al, 2016). It enables researchers to establish links between soil structure and other factors, such as root development (Roger-Estrade et al, 2000a;Mentges et al, 2016), the availability and distribution of minerals (Vizier et al, 1995), and hydrodynamic characteristics (Mentges et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations